The association of smoking and socioeconomic status on melanoma skin cancer. (2nd May 2020) - Gibson, J.A.G.; Dobbs, T.D.; Griffiths, R.; Song, J.; Akbari, A.; Whitaker, S.; Watkins, A.; Langan, S.M.; Hutchings, H.A.; Lyons, R.A.; Whitaker, I.S.
Summary: Skin cancer is the most common cancer type in Western populations and melanoma is the most dangerous form of the disease. In recent years, a link between 'social determinants' and melanoma has emerged. Social determinants encompass both socioeconomic factors (including income, education, poverty level, area of residence, occupation and social status) and lifestyle factors (including exposure to UV light, marital status, hobbies, smoking, obesity). This study carried out by a team of investigators based in Swansea and London in the UK was designed to re‐examine the relationship between people's smoking habits, as well as socioeconomic status, and the occurrence and progression of melanoma. In order to achieve this, the team used a population database that held details of patients diagnosed and treated in Wales. The investigators were able to analyse data from more than 9, 000 patients diagnosed with melanoma over the five years included in this study, and in addition they reviewed information on 26, 000 people without melanoma. They found that smoking was associated with a decreased occurrence of melanoma and that it had no effect on death rates caused by melanoma itself, although death rates due to other causes were higher amongst smokers than non‐smokers. There was also a higher rate of melanoma in people of higher socioeconomic status, but these individuals also had a higher chance of survival from melanoma than those of lower socioeconomic status. The explanation for these findings needs to be clarified, as the differences may be due to a direct effect of smoking on the development and progress of melanoma, or may be related to other factors such as sun exposure rates amongst smokers and non‐smokers. This is a summary of the study: The association of smoking and socioeconomic status on cutaneous melanoma: a population‐based, data‐linkage, case‐control study. Abstract : Linked Article: Gibson et al. Br J Dermatol 2020; 182 :1136–1147